Evaluación de la eficiencia y la productividad en el sector hotelero espa\~nol: Un análisis regional - Pilar Alberca; Laura Parte (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2013)
– This paper analyzes national and regional efficiency and total factor productivity of Spanish hotels. The nonparametric frontier DEA methodology has been used to assess the levels of efficiency of the hotel firms and Malmquist indices to estimate the productive change in the period 2001-2008. The results show the region most efficient and therefore more competitive. The results also show the rates of change in productivity in the period and its main determinants: efficiency change and technical change.
Keywords: L83; D24; O47; M11; 330; Tourism; companies; regional analysis; Competitiveness; Efficiency; Productivity